Belajar Outdoor dan Korelasinya dengan Konsep Islam Hablun Min Al-Alam Pada Pendidikan Usia Dini - Ach. Syaikhu (Auladuna : Jurnal Prodi Pendidikan Guru Madrasah Ibtidaiyah, 2020)
Every human being experiences the learning process that occurs during life between himself and his environment. Therefore, the learning process can be carried out anywhere and anytime. In this paper, the author examines the correlation of the concept of learning outside the environment (Outdoor) with the concept of Islam. As for the closely related relationship in Islam, providing space for children to explore themselves in the external environment as a process of uniting an individual with nature, understanding the concept of nature's work, and fostering a sense of ownership in nature. This paper is expected to be a motivation for teachers to make a joint work to foster critical awareness in children through their active participation in the learning process. By doing learning in an outdoor environment, children will be treated as subjects of learning, have freedom of expression and the opportunity to develop the critical thinking.